Implications of Cow Body Condition Score on Productivity - Matt Hersom; Todd Thrift; Joel Yelich (EDIS, 2015)
Body condition score (BCS) indicates how much fat a cow has on its body, which is an important factor in cow health and reproductive capacity. Growers can use BCS to understand and manage the health of a herd and maintain a profitable operation. This 6-page fact sheet explains how BCS is measured, what different scores mean, the economic impact of various scores, and how changing cow nutrition can move BCS in a desired direction. Written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Sciences, August 2015.